Methodological strategy through the game for teaching pass-reception in basketball/Estratégica metodológica a través del juego para la enseñanza del pase-recepción en baloncesto - Wilson Cristóbal Crespo Guaraca; Danilo Charchabal Pérez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
The teaching-learning process requires didactic strategies that contribute to the acquisition of specific motor habits in an effective way; the game method can contribute considerably to this purpose. In this sense, the objective of the research is to improve the teaching process of pass-reception in basketball through a methodological strategy, using the game method. Two independent groups were formed with 20 male basketball players, each one from the Millennium Educational Unit Nela Martínez Espinosa; a traditional training was implemented to the Control Group and a methodological strategy with six games to the Experimental Group during one semester and the teaching process of the pass-reception was prioritized. The Control Group did not significantly improve the pass-reception technique (p=0.180), unlike the Experimental Group (p=0.000), while, when comparing the results in the post-test between independent groups, the Experimental Group presented a better average range (24.50) than the Control Group (16.50), with a significant difference in its favor (p=0.030). For the present research, a significant improvement in the pass reception technique is achieved in the basketball players of the Experimental Group. It is deduced that the use of a methodological strategy that prioritizes the game method, contributes significantly to the teaching-learning process in the acquisition of specific motor habits of basketball as part of the sports initiation stage.